2022
DOI: 10.3390/lubricants10070139
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication Performance of Sunflower Oil Reinforced with Halloysite Clay Nanotubes (HNT) as Lubricant Additives

Abstract: This study evaluates the tribological performance of nanolubricants of a vegetable oil (sunflower oil) reinforced with different concentrations of environmentally-friendly nanoparticles of halloysite clay nanotubes (HNTs). Tribological characterization was performed under different conditions to determine its effect on the nanolubricants’ performance and optimal HNT concentration. The tribological performances under low and high contact pressures were analyzed with a block-on-ring tribometer following the ASTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…This may be because the polyester film was unstable during the friction process, and the protective effect on the friction surface was weak. 27 Compared with the lubrication of 0.05 wt % CD SFO dispersion (0.05 wt %, 2 N, 200 rpm), the friction curve under 1 wt % NCD SFO dispersion lubrication was more stable, with lower friction coefficient and better lubrication effect. After doping nitrogen, which made the friction chemical reaction better, the resulting compounds further strengthened the protective film of the friction interface and reduced the friction and wear of the surface.…”
Section: ■ Tribological Performance Test Of Ncdsmentioning
confidence: 86%
See 2 more Smart Citations
“…This may be because the polyester film was unstable during the friction process, and the protective effect on the friction surface was weak. 27 Compared with the lubrication of 0.05 wt % CD SFO dispersion (0.05 wt %, 2 N, 200 rpm), the friction curve under 1 wt % NCD SFO dispersion lubrication was more stable, with lower friction coefficient and better lubrication effect. After doping nitrogen, which made the friction chemical reaction better, the resulting compounds further strengthened the protective film of the friction interface and reduced the friction and wear of the surface.…”
Section: ■ Tribological Performance Test Of Ncdsmentioning
confidence: 86%
“…SFO not only has biodegradability, renewability, and environmental friendliness but also produces free fatty acids through oxidative degradation during the friction process, which is easy to form a friction polyester film with anti-wear and anti-friction effects on the friction surface. , Therefore, SFO is expected to become an environmentally friendly high-performance base oil. In addition, PAO10 is often used as a base oil to explore the effect of additives on its tribological properties. By comparing the friction curves of SFO, PAO10, PAO4, and paraffin oil lubrication, it can be found that SFO and PAO10 show good friction reduction (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation